PENATALAKSANAAN PASIEN DIABETES MELITUS DI POLIKLINIK RUMAH SAKIT SANGLAH DENPASAR - Adnyana, Losen; -, Hensen; Gde Budhiarta, Anak Agung (journal of internal medicine, 2006)
A cross-sectional study was conducted from March until May 2003 among 100 diabetic patients, registered inDiabetic Clinic, Department of Internal Medicine Sanglah Hospital for management of diabetes for more than 12months. Primary objective was to evaluate diabetes control, diabetes management and late complications status in thediabetic population managed by Diabetic Clinic as urban health care clinics. The subjects were 65% men and 35%women with mean of age 59.4 years and known having diabetes since 1-5 years (mean 2.1 years). Samples consist of4% type-1 diabetes; 95% type-2 diabetes and 1% gestational diabetes. Antidiabetic medication were sulfonylurea67%; metformin 55%; insulin 26% and others (glucosidase inhibitors, thiazolidenedione and others) were 0%.According to the level of AIC, lipid profile and blood pressure, 40% (AIC < 6.5%); 50% (HDL-chol >-45 mg/dl);27.0% (LDL-cho! < 100 mg/dl); 67.6% (triglyceride < 150 mg/dl) and 23% (blood pressure < 130/80 mmHg) werecategorized as good diabetic controls. Large proportion of poor diabetic controls partly may be due to low proportionof education days received on diabetes in the past year (57% have only I education day and 32% with zero educationday). This condition also impact on lifestyle modification where 63% not regularly and 14% never follow the diet and50% never . exercise. Also 12% still smoker and 4% sti 11 consume alcohol on a regu lar basis. Micral test to detectmicroalbuminuria as an early I phase of diabetic nephropathy were not commonly used (7%), and dipstick to detectmakroalbuminuria (99%). Blood test for serum creatinin showed 89% with serum creatinin <2 mg/dl and 11% withserum creatinin >2 mg/dl. Another chronic complication were neuropathy (10.1%); cataract (10.4%); backgroundretinopathy (8.6%), healed ulcer (3%), stroke (2%), leg amputation (1%), absence of foot pulse (1%), acuteulcer/gangrene (1%), myocard infard/CABG/angioplasty (1%).